Ketentuan Hukum Merek Wellknown Mark Dalam Pemberlian Melalui Online - Debora; Jinner Sidauruk; Lesson Sihotang; Marthin Simangunsong (Jurnal Visi Pengabdian Kepada Masyarakat, 2022)
Information technology related to online business transactions is growing very rapidly. Business actors and consumers, both in urban centers and in areas, use information technology to shop or transact, including transactions for goods labeled with Well Known Marks (Famous Brands) that are protected by Trademark Law, which are traded through online system facilities. In online transactions related to well-known brand products, there are still violations that are detrimental to the brand owner. In connection with this, it is important to conduct socialization to the community, including teenagers who are also very potential consumers of branded goods that are traded through the internet. Nationally, Well Known Marks in Indonesia are regulated based on Article 4 and Article 6 of Law no. 20 of 2016 concerning Brands. Meanwhile at the international level the provisions governing Famous Marks are through the provisions of Article 6bis of the Paris Convention and Article 16 (2) of the TRIPs Agreement. Online business transactions in Indonesia are regulated by Law no. 11 of 2008 concerning Information and Electronic Transactions. In connection with the rapid development of transaction practices for well-known branded goods through the online system, for the sake of legal protection for both well-known brand owners and consumers, especially teenagers who tend to be adaptive to changes in new trends, it is important to understand the legal provisions, both trademark law and trademark law. information technology law as regulated in UU No. 20 of 2016 and the U.U. No. 11 of 2008 and PP No. 71 Year 2019